Recent Advances in Flexible Ultrasonic Transducers: From Materials Optimization to Imaging Applications - Danyang Ren; Yonggang Yin; Chiye Li; Ruimin Chen; Junhui Shi (Micromachines, 2023)
Ultrasonic (US) transducers have been widely used in the field of ultrasonic and photoacoustic imaging system in recent years, to convert acoustic and electrical signals into each other. As the core part of imaging systems, US transducers have been extensively studied and achieved remarkable progress recently. Imaging systems employing conventional rigid US transducers impose certain constraints, such as not being able to conform to complex surfaces and comfortably come into contact with skin and the sample, and meet the applications of continuous monitoring and diagnosis. To overcome these drawbacks, significant effort has been made in transforming the rigid US transducers to become flexible and wearable. Flexible US transducers ensure self-alignment to complex surfaces and maximize the transferred US energy, resulting in high quality detection performance. The advancement in flexible US transducers has further extended the application range of imaging systems. This review is intended to summarize the most recent advances in flexible US transducers, including advanced functional materials optimization, representative US transducers designs and practical applications in imaging systems. Additionally, the potential challenges and future directions of the development of flexible US transducers are also discussed.